2011
DOI: 10.1111/j.2044-8341.2011.02046.x
|View full text |Cite
|
Sign up to set email alerts
|

Fears of compassion and happiness in relation to alexithymia, mindfulness, and self‐criticism

Abstract: While the development of positive emotions, especially those linked to affiliation and connectedness are increasingly seen as important therapeutic targets, little research has focused on the blocks and fears to positive emotions. This study used newly developed fears of positive affect scales (e.g., compassion and happiness) to explore these aspects and found they were significantly linked to psychopathology variables self-criticism and difficulties such as alexithymia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
195
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(220 citation statements)
references
References 48 publications
20
195
0
5
Order By: Relevance
“…Positive emotions can be associated with negative outcomes particularly in children who have been punished at times when they have been enjoying themselves [24]. In a recent study in a student population, Gilbert et al [21] found that fear of happiness is strongly correlated with depression. Beblo et al [9] also found that fear and suppression (inhibiting the outward signs of inner feelings) of positive and negative emotions were linked to depressive symptoms.…”
Section: Positive Emotionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Positive emotions can be associated with negative outcomes particularly in children who have been punished at times when they have been enjoying themselves [24]. In a recent study in a student population, Gilbert et al [21] found that fear of happiness is strongly correlated with depression. Beblo et al [9] also found that fear and suppression (inhibiting the outward signs of inner feelings) of positive and negative emotions were linked to depressive symptoms.…”
Section: Positive Emotionsmentioning
confidence: 97%
“…An increasing number of studies has also found that some people can have a fear of 'positive emotions', such as feeling safeness, happiness, and affiliative emotions associated with compassion [9,[20][21][22]. Arieti and Bemporad [23] suggested that some depressed patients have what they called 'a taboo on pleasure' and are fearful of positive emotions.…”
Section: Positive Emotionsmentioning
confidence: 99%
“…Gilbert et al developed a measure of 'fears of compassion' and found them to be highly correlated to psychopathology symptoms. In a follow-up study, Gilbert et al [52] found fears of compassion to be linked to fears of happiness in general, and problems with emotional processing (alexithymia) and mindfulness. This studies of the fears of compassion to date however have been with non-clinical populations.…”
Section: Fears Blocks and Resistances To Compassionmentioning
confidence: 99%
“…So it is plausible that difficulties with empathy and mentalising will also compromise compassion [52].…”
Section: Fears Blocks and Resistances To Compassionmentioning
confidence: 99%
See 1 more Smart Citation